Statistical model of in-vehicle sound generated from highway rumble strips. (22nd January 2010) - Donnell, Eric T.; Sommer, H. Joseph; Garvey, Philip M.; Himes, Scott C.; , Darren J. Torbic
Shoulder and centreline rumble strips are used on highways in the USA to prevent single-vehicle run-off-road and opposite direction crashes. Both rumble strip types have been shown to provide positive safety benefits on a variety of roadway types. The elevated in-vehicle sound and vibration levels produced by rumble strip patterns provide the alerting properties to warn drivers that their vehicles have left the intended travel lane. This study estimated a model of in-vehicle sound intensity, frequency, and duration using seemingly unrelated regression. The statistical model indicates that increasing the vehicle speed; rumble strip length, width, and groove depth; and using a milled versus a rolled rumble strip pattern, all increase the in-vehicle sound level relative to the ambient level. A rumble strip on the right-side of the travel lane; increasing the vehicle angle of departure; increasing the centre-to-centre spacing of the grooves; a concrete roadway surface; and a wet roadway surface, all decrease the in-vehicle sound relative to the ambient sound.